2022
DOI: 10.1016/j.ctro.2021.10.006
|View full text |Cite
|
Sign up to set email alerts
|

A prospective behavioral and imaging study exploring the impact on long-term memory of radiotherapy delivered for a brain tumor in childhood and adolescence

Abstract: Highlights Common long-term memory defects after pediatric brain tumor affect school achievement The hippocampi, the cerebellum and cerebellar-cortical networks play a role in several memory systems. This study will provide long-term neuropsychological data about four different memory systems. We will investigate the correlations between neuropsychological, neuroimaging and radiotherapy dose data. Imaging will be struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…We did not find any significant associations between cognitive disorders and radiation doses to the brain or the hippocampi. Several studies have shown that the decline in cognitive activity can be attributed to multiple additional risk factors, such as the radiation dose [47] , but also tumour-induced hydrocephaly, young age at diagnosis, hearing loss, or post-operative posterior fossa syndrome [48] , [49] , [50] . Pre-existing neurological deficiencies frequently were frequent prior to undergoing radiation therapy, this is predominantly due to the tumour itself and/or the surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find any significant associations between cognitive disorders and radiation doses to the brain or the hippocampi. Several studies have shown that the decline in cognitive activity can be attributed to multiple additional risk factors, such as the radiation dose [47] , but also tumour-induced hydrocephaly, young age at diagnosis, hearing loss, or post-operative posterior fossa syndrome [48] , [49] , [50] . Pre-existing neurological deficiencies frequently were frequent prior to undergoing radiation therapy, this is predominantly due to the tumour itself and/or the surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need to set dose constraints on the specific brain areas involved in memory to further reduce the impact of radiotherapy on learning and memory. We are currently conducting a prospective study to develop methods to define theses dose constraints [64]. However, radiotherapy is not the only prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…ASL-weighted perfusion maps and CBF maps are of interest for exploring, assessing, and quantifying brain tumors in pediatric patients before and after treatment. They should make it possible to limit the dose of irradiation to some structures and organs at risk in pediatric patients and by so doing limit the risks of cognitive sequelae after treatment [66]. Moreover, there are currently no established fluorescent stains that allow intraoperative imaging in pediatrics brain tumors.…”
Section: Discussionmentioning
confidence: 99%